2014
DOI: 10.17219/acem/37331
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Intraabdominal Pressure Protocols in Laparoscopic Procedures on Oxidative Stress Markers and Morphology in Rat Ovaries

Abstract: Background. To determine the effects of different intraabdominal pressure (IAP) on the ovaries in a laparoscopic rat model. Objectives. The aim of the study was to determine the effects on the ovaries of different intraabdominal pressures (IAP) in laparoscopic surgery in a rat model. Material and Methods. Thirty-two post-pubertal nonpregnant Sprague-Dawley rats were divided randomly into four groups. In the control group, no intraabdominal pressure (IAP) was applied. In Group Pp10 and Group Pp15, an IAP of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Although it was not the purpose of the study to examine the attenuate techniques for testicular damage during pneumoperitoneum, preconditioning studies of pneumoperitoneum were not found. Preconditioning uses brief exposure to IAP prior to the main procedure, where animals subjected to pneumoperitoneum carried out with pressure of 15 mmHg and TE of 1 hour showed lower degrees of ovarian lesions when compared to animals without pre-conditioning (Biler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although it was not the purpose of the study to examine the attenuate techniques for testicular damage during pneumoperitoneum, preconditioning studies of pneumoperitoneum were not found. Preconditioning uses brief exposure to IAP prior to the main procedure, where animals subjected to pneumoperitoneum carried out with pressure of 15 mmHg and TE of 1 hour showed lower degrees of ovarian lesions when compared to animals without pre-conditioning (Biler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Operation trauma is a strong stressor that can significantly activate the body's stress response and cause the abnormal synthesis and secretion of a variety of endocrine hormones [10][11]. Adrenal gland is the endocrine gland that plays an important role in the process of stress reactio, the hormones secreted by adrenal medulla and cortex are closely related to the activation of stress reaction [12].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal gland is an endocrinal organ that plays an important role in the process of stress reaction. E and NE secreted by adrenal medulla and Cor secreted by adrenal cortex are the important endocrine hormones mediating stress reaction [17,18]. When the body is suffering from external trauma, hypothalamicpituitaryadrenal (HPA) axle will be activated and the sympathetic nerve activity is enhanced [19,20].…”
Section: Discussionmentioning
confidence: 99%